2016
DOI: 10.1161/atvbaha.115.306710
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 1α Is a Critical Downstream Mediator for Hypoxia-Induced Mitogenic Factor (FIZZ1/RELMα)–Induced Pulmonary Hypertension

Abstract: Objective Pulmonary hypertension (PH) is characterized by progressive elevation of pulmonary vascular resistance, right ventricular failure, and ultimately death. We have shown that in rodents, hypoxia-induced mitogenic factor (HIMF; also known as FIZZ1 or RELMα) causes PH by initiating lung vascular inflammation. We hypothesized that hypoxia-inducible factor-1 (HIF-1) is a critical downstream signal mediator of HIMF during PH development. Approach and Results In this study, we compared the degree of HIMF-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 60 publications
(97 reference statements)
1
59
0
Order By: Relevance
“…While the role of innate immune pathways including NFKB, IL1B, IL6, toll like receptor signaling, interferon gamma, HIF-1, and STAT3 signaling are well described with regard to their roles in pulmonary hypertension, very little is known within the context of macrophages in PH (9, 4654). We previously demonstrated that ex-vivo fibroblasts isolated from neonatal calves and humans with PH polarize macrophages via paracrine IL-6 to a phenotype characterized by increased expression of STAT3, HIF1, and Arginase 1(9).…”
Section: Discussionmentioning
confidence: 99%
“…While the role of innate immune pathways including NFKB, IL1B, IL6, toll like receptor signaling, interferon gamma, HIF-1, and STAT3 signaling are well described with regard to their roles in pulmonary hypertension, very little is known within the context of macrophages in PH (9, 4654). We previously demonstrated that ex-vivo fibroblasts isolated from neonatal calves and humans with PH polarize macrophages via paracrine IL-6 to a phenotype characterized by increased expression of STAT3, HIF1, and Arginase 1(9).…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide a clue for understanding why PAH patients are likely to be complicated by coronary artery disease even in the absence of metabolic disorders. Johns et al 65 showed that hypoxia-inducible factor-1 was an important downstream mediator of hypoxia-induced mitogenic factors that contributed to the development of pulmonary hypertension, in part, through pulmonary microvascular endothelial cell activation, apoptosis, and inflammation.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…Finally, it might be considered that HIF2-dependent actions in bronchial epithelium could contribute not only for local airway adaptation to hypoxia, but also to more distant pulmonary vessel remodeling described above. In this line, hypoxia-induced RELM-α (largely produced in bronchial epithelium) causes PH characterized by an increase in mean pulmonary artery pressure, pulmonary vascular resistance, right heart hypertrophy, and vascular remodeling caused by chronic hypoxia as well as lung vascular inflammation [ 63 , 64 ]. At molecular level, RELMα also recruits bone marrow-derived macrophages, promotes IL-6 expression in PASMC and macrophages through HIF1α and favors vascular remodeling associated to PH [ 63 , 64 ].…”
Section: Role Of Hif Pathway In the Airway Epitheliummentioning
confidence: 99%